Pharmacokinetic study of isoquercitrin in rat plasma after intravenous administration at three different doses (Brazilian Journal of Pharmaceutical Sciences, 2013)
The aim of this study is to develop a simple and specific HPLC method using vitexin as the internal standard to investigate the pharmacokinetics of isoquercitrin (ISOQ) after three different doses administrated intravenously to rats. The pharmacokinetic parameters were calculated by both compartmental and non-compartmental approaches. The results showed that ISOQ fitted a three-compartment open model. The values of AUC increased proportionally within the range of 5-10 mg·kg-1. Moreover, a half-life, b half-life, ªCL, MRT0-t and MRT0→∞ of ISOQ in rats showed significant differences between 20 mg·kg-1 and other doses, indicating that ISOQ presented dose-dependent pharmacokinetics in the range of 5-10 mg·kg-1 and non-linear pharmacokinetics at higher doses.